A novel biomarker‐based analysis reliably predicts nodal metastases in anal carcinoma: preliminary evidence of therapeutic impact. (November 2013) - Mistrangelo, M.; Senetta, R.; Racca, P.; Castellano, I.; Chiusa, L.; Bellò, M.; Ricardi, U.; Morino, M.; Cassoni, P.
Abstract Aim Routine prophylactic inguinal irradiation in anal cancer may cause significant toxicity associated with overtreatment bias. The aim of this study was to determine the risk of regional node metastases in anal carcinoma by identifying predictive molecular biomarkers. Method Clinicohistopathological data from 50 pretreatment anal carcinoma biopsies were collected. Immunohistochemical analyses with antibodies against Ki67, p53, epidermal growth factor receptor (EGFR) and YKL‐40 were performed. Statistical correlations between biomarkers and clinicopathological features and outcomes were studied. Sentinel lymph node biopsy was performed in a subset of 36 patients. Results All patients had undergone synchronous radiochemotherapy; tumour recurrence had developed in 26%, and 16% had died. YKL‐40 tumour expression correlated with lymph node metastasis, whereas no inguinal node metastases were found in any of the (14%) patients presenting with a YKL‐40/EGFR‐negative tumour. YKL‐40 expression and node metastasis were both significantly associated with shorter overall and disease‐free survival. Tumour grade significantly correlated with disease‐free survival only. HIV, tumour histological type, Ki67, p53 and EGFR were not associated with outcome. Conclusion YKL‐40 expression in anal carcinoma is correlated with a poor outcome and can predict lymph node metastases. The combined absence of YKL‐40 and EGFR expression in a first biopsy of anal carcinoma reliably selects a subset of patients without inguinal metastases. Such patients could be spared sentinel lymph node biopsy and/or inguinal radiotherapy.